Clinical assessment of SARS-CoV-2 antigen rapid detection compared with RT-PCR assay for emerging variants at a high-throughput community testing site in Taiwan. (February 2022) - Jian, Ming-Jr; Perng, Cherng-Lih; Chung, Hsing-Yi; Chang, Chih-Kai; Lin, Jung-Chung; Yeh, Kuo-Ming; Chen, Chien-Wen; Hsieh, Shan-Shan; Pan, Pin-Ching; Chang, Hao-Ting; Chang, Feng-Yee; Ho, Ching-Liang; et al.
Highlights: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) B1.1.7 lineage was prevalent in April 2021 and spread into Taiwan. The coronavirus disease 2019 (COVID-19) Antigen Rapid Test Kit (ART) can detect SARS-CoV-2 B.1.1.7 variants. ART can be used in densely populated areas for symptomatic or asymptomatic subjects. ART and RT-PCR combined can improve COVID-19 diagnosis and curb community transmission. ABSTRACT: Objectives: With the emergence of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) B.1.1.7 lineage in the ongoing coronavirus disease 2019 (COVID-19) pandemic, Taiwan confronted a COVID-19 flare up in May 2021. Large-scale, accurate, affordable and rapid diagnostic tests such as the lateral flow assay can help to prevent community transmission, but their performance characteristics in real-world conditions and relevant subpopulations remain unclear. Methods: The COVID-19 Antigen Rapid Test Kit (Eternal Materials, New Taipei City, Taiwan) was used in a high-throughput community testing site; the paired reverse transcription polymerase chain reaction (RT-PCR) results served as a reference for sensitivity and specificity calculations. Results: Of 2096 specimens tested using the rapid antigen test, 70 (3.33%) were positive and 2026 (96.7%) were negative. This clinical performance was compared with the RT-PCR results. The sensitivity and specificity of the rapid antigen test were 76.39% [95% confidence interval (CI) 64.91–85.60%] and 99.26% (95% CI 98.78–99.58%), respectively, with high sensitivity in subjects with cycle threshold values ≤24. Further, the rapid antigen test detected the SARS-CoV-2 B.1.1.7 lineage effectively. Conclusions: Considering the short turnaround times and lower costs, this simple SARS-CoV-2 antigen detection test for rapid screening combined with RT-PCR as a double confirmatory screening tool can facilitate the prevention of community transmission during COVID-19 emergencies.